2008
DOI: 10.1177/0363546508326712
|View full text |Cite
|
Sign up to set email alerts
|

Glenohumeral Internal Rotation Deficits in Baseball Players with Ulnar Collateral Ligament Insufficiency

Abstract: Our results indicate that pathologic glenohumeral internal rotation deficit may be associated with elbow valgus instability. This has important clinical implications both in terms of preventing ulnar collateral ligament injury and with regard to rehabilitating throwers after ulnar collateral ligament reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
193
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(206 citation statements)
references
References 27 publications
5
193
8
Order By: Relevance
“…Even considering the pre-established context in which handball athletes who perform a large number of shots and passes can present an upward trend of ROM external rotation and reduction in WMD internal rotation of the dominant glenohumeral joint (5,6) in the present study no significant difference or treatment effect was observed for increased internal rotation or reduction in external rotation at the shoulder of the athletes. It is thought that the small effect generated by NEB may be related to the high muscular fitness, together with the low level of disability and mild pain of the athletes evaluated.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Even considering the pre-established context in which handball athletes who perform a large number of shots and passes can present an upward trend of ROM external rotation and reduction in WMD internal rotation of the dominant glenohumeral joint (5,6) in the present study no significant difference or treatment effect was observed for increased internal rotation or reduction in external rotation at the shoulder of the athletes. It is thought that the small effect generated by NEB may be related to the high muscular fitness, together with the low level of disability and mild pain of the athletes evaluated.…”
Section: Discussioncontrasting
confidence: 70%
“…These disorders are triggered by microinjuries generated by repetitiveness and may result in prejudice to performance of the sport gesture and hence athlete performance. The most common alterations found are the onset of pain, shoulder instability, scapular dyskinesia (1) , an increased range of motion (ROM) of external rotation and a reduction in ROM of internal rotation of the glenohumeral joint in the dominant shoulder performing the throwing gesture (5,6) . Recent investigations in handball athletes point to the need to carry out rehabilitation programs that aim to improve the instability of the glenohumeral joint, widely used in the various tasks of this modality (7,8) .…”
Section: Introductionmentioning
confidence: 99%
“…Dines et al 4) reported that adolescent pitchers with side-to-side differences in shoulder IR ROM of >13° had 6 times greater risk of throwing injuries. Shanley et al 5) reported that a shoulder IR ROM deficit on the throwing side was 15.8° greater in players with ulnar collateral ligament insufficiency than in those who were asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we conclude that the shoulder IR ROM deficit in our study is a change that appears in baseball players in general. However, a notable change in shoulder IR ROM provokes medial elbow injuries 4,5) . Muscular tightness 3,34) , posterior capsular tightness 35,36) , and scapular position 37) induced by repetitive throwing are all involved in shoulder IR ROM deficits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation